Perencanaan Struktur Gedung Supermarket Berlantai Tiga Di Wamena - Wika Matana Nion; Juliana Br. Simangunsong (Jurnal Sipil Terapan, 2023)
As a buffer for districts in the Central Mountain region of Papua, Wamena has also become a center of economic and government activity so that Wamena needs shopping facilities on a large scale in order to meet the needs of its population, therefore it is necessary to plan shopping facilities on a larger scale such as supermarkets. The purpose of this study was to plan the Upper Structure of the Berlantai Tiga di Wamena Supermarket Building. The planning of this supermarket includes plates, beams and columns. The tools used in this planning are ETABS v.19, AutoCad and Microsoft Office. The location of the building is on Jalan Trikora Wamena, Papua. The result of the structural design uses the Special Moment Bearing Frame System (SRPMK). Using concrete quality (f'c) = 25 MPa and reinforcement quality (fy) = 420 MPa. Floor slabs are used 170 mm thick and roof slabs with 130 mm thick. The beam uses B1 300 x 400 mm, B2 300 x 350 mm, B3 250 x 300 mm. The columns in the design measure 600 x 600 mm.